Relationship between kinematic variability and performance in basketball free-throw - Coves, A.; Caballero, C.; Moreno, F. J. (International Journal of Performance Analysis in Sport, 2020)
Basketball Free-throw analysis has been approached from different research areas, trying to explore if an ideal throw pattern exists or if the throwing movement responds to different patterns depending on players` characteristics. Nevertheless, not only are there differences in the technique between players, but they also show intrinsic variability in a series of throws. The relationship between inter- and intra-individual variability in kinematics and performance and the exploration of the existence of kinematic variables that can characterise successful throw patterns were analysed. Kinematic variables of 20 participants performing free-throws were analysed, finding that each player has an individual release pattern, adapted to his/her characteristics. Therefore, training should be adapted to his/her individualities. Nonetheless, the higher hand velocity at the time of the ball release was the main relevant variable for succeeding. Regarding the variability and performance relationship, not all players achieved success when their throwing technique was close to their average pattern. This study may influence the way in which technique training exercises are designed, stressing the significance of allowing the player to explore among the different options of his/her motor perceptual system, finding those configurations which are more suitable to his/her characteristics.